A location-aware power control mechanism for interference mitigation in M2M communications over cellular networks. (December 2020) - Das, Sree Krishna; Hossain, Md Farhad
Highlights: A novel location-aware communication mode selection based power control mechanism is proposed for mitigating interference in M2M communications over cellular networks. Location-aware resource allocation between the MUEs and CUEs that share the resource in both orthogonal and non-orthogonal ways are analyzed for different modes. A water filling algorithm and Lagrange decomposition scheme based power optimization process are adopted for allocating the proper optimal transmit power to each UE in the proposed mechanism. Extensive simulation results are carried out for evaluating the performance of the proposed mechanism. The orthogonal resource sharing scheme based proposed mechanism can substantially improve the system performance in terms of per-user energy efficiency (EE) compared to the non-orthogonal resource sharing scheme based proposed mechanism. Graphical abstract: Abstract: Machine-to-Machine (M2M) communication is considered as a promising technology in fifth-generation (5G) cellular networks to reduce the power consumption and improve energy efficiency. To achieve these benefits, identification of unknown machine location is crucial for mitigating interference. Therefore, this paper proposes a location-aware communication mode selection based power control mechanism for reducing interference in M2M communications over cellular networks. The proposed mechanism depends on the threshold distance while communicating among M2M pair. Consequently, user equipment (UE) selects the proper communication mode in the proposed mechanism. Resource allocation between the M2M UEs (MUEs) and cellular UEs (CUEs) that share the resources in both orthogonal and non-orthogonal ways are analyzed for different modes. A water filling algorithm and Lagrange decomposition scheme based power optimization process are adopted for allocating the proper optimal transmit power to each UE in the proposed mechanism. Simulation results are compared with the non-orthogonal and orthogonal resource sharing scheme based proposed mechanism which shows that the orthogonal resource sharing scheme provides better system performance in the proposed network.